Experimental and Simulated Study of Ammonia Combustion at High Pressures - García Ruiz, Pedro; Uruen; Alzueta, Uxue; Abián, María (Jornada de Jóvenes Investigadores del I3A, 2022)
Ammonia can be burned directly without CO2 emissions. The present work deals with the experimental and simulated study of the NH3 conversion at high pressures at two oxygen excess ratios (lambda, l) 1 and 3, and different pressures (from 10 to 40 bar).